Special Issue on Voting Advice Applications and State of the Art: Theory, Practice, and Comparative Insights - Chadjipadelis, Theodore; Triga, Vasiliki; Serdult, Uwe (My University, 2012)
Online voting tools, increasingly known as voting advice (aid) or engagement applications (VAAs or VEAs), progressively have been used in numerous European countries with the objective of offering to prospective voters a matching with the candidates/parties, providing clear information regarding the party/candidate agendas and clarifying the positions of candidates/parties on a series of policy issues. Although such tools have been initially used in the Netherlands and Germany, very soon they have penetrated many other national contexts with great success. They have been deployed in different types of electoral contests, like national presidential or parliamentary elections as well as less salient elections, like the elections for the European Parliament or regional elections. Despite the claim that such tools are considered especially adapted to multi- party electoral settings rather than to two party systems (e.g. the US with its Republican/Democrat contest) (Raimonaite 2010), they can still be useful by being candidate instead of party-based.